Menelaah Makna Tarian Adat Ro'a Mu'u dalam Upacara Perkawinan Adat dan Hubungannya dengan Pemberkatan Perkawinan Gereja di Desa Wolomapa Paroki Mater Boni Consili Watublapi - Dolvina Liskelia Sao; Graciana Amanda Bele; Gerardus B. Duka (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research is motivated by the importance of preserving local cultural values ​​that live in society and their relevance to the life of the faith of Catholics. This research uses a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation, in-depth interviews with 9 informants, namely traditional leaders, church leaders, married couples, and local communities, as well as documentation studies. The results of the study show that the traditional ro'a mu'u dance contains noble values ​​that are passed down from generation to generation. This dance is a symbol of acceptance, unity, respect, towards the dignity of the bride and groom and family, as well as an expression of gratitude for the formation of a new family. In addition, the traditional ro'a mu'u dance reflects the values ​​of togetherness, loyalty, responsibility, love, and harmony in family life. These values ​​are closely related to the meaning of the Catholic Church's marriage blessing which emphasizes the bond of love between husband and wife as a life partnership based on love, loyalty, and openness to God's work. Based on the research results, it can be concluded that the traditional ro'a mu'u dance is closely related to church wedding blessings because both emphasize the values ​​of unity, loyalty, responsibility, and togetherness in building a family. This dance also serves as a form of inculturation that enriches the faith of Catholics without diminishing local cultural identity. Therefore, the traditional ro'a mu'u dance deserves to be preserved as a cultural heritage with social, cultural, and religious value.